Sense of Community: A Thematic Review on Neighbourhood Built Environment - Azli, Mohd; Abdullah, Jamalunlaili; Abdullah, Yusfida Ayu; Shukri, Sharyzee Mohmad; Sahabuddin, Mohd Firrdhaus Mohd; Abdullah, Azli; Taib, Idris (MAJ - Malaysia Architectural Journal, 2024)
Sense of Community: A Thematic Review on Neighbourhood Built Environment